The digital agricultural plot to help Guatemalan farmers resist climate change - Lizarazo Torres, Miguel Angel; Ramos Solorzano, Gresia Dalal; Jimenez Rodas, Daniel Ricardo (2024)
Learn about the Digital Plot hosted at CUNORI (Universidad de Oriente) in Guatemala, an experimental and participatory space exploring how digital technologies can serve smallholder farmers in the Central American Dry Corridor.